SONOPORATION: THERAPEUTIC AID USING ULTRASONIC WAVES - Dr Pradkhshana Vijay; Dr. Shaleen Chandra; Dr. Diksha Singh; Dr. Priyanka Singh; Dr Supriya Sharma (Medico Research Chronicles, 2018)
Ultrasound, a traditional diagnostic modality has emerged as a budding non-invasive tool for drug delivery, gene therapy, and other therapeutic techniques. It is a mechanical wave energy generated in a medium as the oscillating pressure at frequencies above 20 kHz which is beyond the audible range. This exposure causes tissue heating, shear stress, and cavitation, which have been deployed for therapeutic usage. One such ultrasound technique is Sonoporation that employs the acoustic cavitation of micro bubbles generating transient pores on membrane enhancing delivery of large molecules into cells for targeted drug delivery and gene transfection. This review provides the main findings in the field of sonoporation, namely drug delivery, gene delivery, DNA transfer and its possible clinical application in dentistry